2005
DOI: 10.1007/s10495-005-1875-2
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions and the propagation of cell survival and cell death signals

Abstract: Gap junctions are a unique type of intercellular channels that connect the cytoplasm of adjoining cells. Each gap junction channel is comprised of two hemichannels or connexons and each connexon is formed by the aggregation of six protein subunits known as connexins. Gap junction channels allow the intercellular passage of small (< 1.5 kDa) molecules and regulate essential processes during development and differentiation. However, their role in cell survival and cell death is poorly understood. We review exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
119
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(122 citation statements)
references
References 126 publications
(158 reference statements)
3
119
0
Order By: Relevance
“…Indeed, plasma membrane collapse during primary or secondary necrosis is associated with the release of RNA molecules, which interact with TLR3 on DCs, 101 with the release of double-stranded DNA, 102 which stimulates both macrophages and DCs, as well as that of nucleotides, leading to the maturation of DCs 103 along with the activation of the NF-kB pathway. 104 End-stage degradation products from dying tumor cells are able to modulate their recognition by the immune system through a family of innate immunity receptors, the pentraxins.…”
Section: End-stage Degradation Products With Proinflammatory Propertiesmentioning
confidence: 99%
“…Indeed, plasma membrane collapse during primary or secondary necrosis is associated with the release of RNA molecules, which interact with TLR3 on DCs, 101 with the release of double-stranded DNA, 102 which stimulates both macrophages and DCs, as well as that of nucleotides, leading to the maturation of DCs 103 along with the activation of the NF-kB pathway. 104 End-stage degradation products from dying tumor cells are able to modulate their recognition by the immune system through a family of innate immunity receptors, the pentraxins.…”
Section: End-stage Degradation Products With Proinflammatory Propertiesmentioning
confidence: 99%
“…In pathological conditions, astrocytes become activated, via the upregulation of glial fibrillary acid protein (GFAP), and have been demonstrated to be capable of protecting neurons from various injuries, including trauma and ischemic insult (18)(19)(20)(21). GJC, the molecular channel allowing the transmission of critical survival-associated secondary messengers, has been shown to be one of the mechanisms underlying this process (22,23). Previous studies have suggested that there are activated astrocytes surrounding glioma cells, and that functional GJC exists between astrocytes and glioma cells (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of gap junctions prevents cell death (Farahani et al, 2005;de Pina-Benabou et al, 2005;Krysko et al, 2005). We, for the first time, show that PKCγ C1B mutations have a negative effect on endogenous wild type PKCγ.…”
Section: Discussionmentioning
confidence: 65%
“…Loss of control of gap junctions by PKCγ, ie., no PKCγ phosphorylation of Cx50 in PKCγ knockout lenses, causes PKCγ knockout lenses to be more susceptible to oxidative stress-induced cataracts in the mouse (Lin et al, 2006). Inhibition of gap junctions prevents cell death (Farahani et al, 2005;de Pina-Benabou et al, 2005;Krysko et al, 2005). It is apparent that control of gap junctions is essential for lens cell survival.…”
Section: Introductionmentioning
confidence: 99%